Isolation and partial characterization of concanavalin A receptors on cloned cytotoxic T lymphocytes. - Sitkovsky, M V (1984)
A small set of concanavalin A (Con A)-binding glycoproteins was isolated from the surface membrane of cloned cytotoxic T lymphocytes (CTL) and partly identified using monoclonal antibodies. The binding of Con A by these glycoproteins on the CTL surface results in the secretion of gamma-interferon and in blocking the effector functions of the cells-namely, antigen-specific and lectin-dependent cytotoxicity. The Con A is evidently bound tightly to some surface structures ("Con A-receptors") that are required for the activation and cytotoxic activity of CTL. To isolate and identify these receptors, antibodies to Con A were used. After Con A was allowed to bind to radiolabeled cloned CTL (labeled with 125I or [35S]methionine or 3H-labeled amino acids), the cells were washed thoroughly, lysed in detergents and anti-Con A antibodies were added to bind to the Con A-receptor complexes. The resulting aggregates were adsorbed with protein A-bearing Staphylococci and the receptors were then specifically released from the pelleted bacteria by alpha-methyl-D-mannoside and analyzed by polyacrylamide gel electrophoresis under reducing conditions. Eight to nine labeled components were seen by autoradiography and with the aid of monoclonal antibodies to known T-cell surface molecules, four were identified as T200, lymphocyte function-associated antigen (LFA)-1, alpha- and beta-chains, and (on some clones) Lyt-2. Other components with Mr congruent to 160,000, 120,000, 46,000, 42,000, and 23,000 have not been identified. The procedures described here may have general application in the studies of the functional properties of other cell surface molecules.